Are school-based behavioural interventions an effective strategy for improving physical activity and sedentary behaviour in children and adolescents? A meta-analysis - Guo, Liangru; He, Hengwang; Wang, Chaochao (Frontiers in Pediatrics, 2025)
ObjectiveThis systematic evaluation and meta-analysis [PROSPERO CRD42024598218] was conducted in order to summarise the effectiveness of a body of school-based behavioural interventions on physical activity (PA) and sedentary behaviour in children and adolescents.MethodsWe conducted a systematic search of the literature up to November 2024 using PubMed, Web of Science and SCOPUS. The methodological quality of the included literature was assessed using the Cochrane Risk Assessment Tool.ResultsOf the 6,071 search records initially identified, 26 studies were considered eligible for systematic evaluation and meta-analysis. School-based behavioural interventions were effective in increasing moderate-intensity physical activity [standardised mean difference (SMD), 0.18 (95% CI, 0.04–0.31), p = 0.01]. School-based behavioural interventions failed to reduce ST (sedentary time) [−0.04 (95% CI, −0.08 to −0.01), p = 0.12] and failed to improve low-intensity PA (LPA) [0.18 (95% CI, −0.07–0.44), p = 0.16]. Subgroup analyses showed that school-based behavioural interventions were more effective in improving moderate-intensity PA in children and adolescents who were in school [0.46 (95% CI, 0.20–0.72), p = 0.02]. School-based behavioral interventions do not differentiate moderate-intensity physical activity among children and adolescents of different ages, [0.18 (95% CI, 0.05–0.31), p = 0.1], nor do they make a difference in moderate-intensity physical activity among children and adolescents in different regions [0.18 (95% CI, 0.04–0.31), p = 0.12].ConclusionSchool-based behavioural interventions are effective in increasing moderate-intensity PA among children and adolescents, particularly those who were in school.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, PROSPERO [CRD42024598218].